Related Factors in Exclusive Breastfeeding of Plywood Workers of PT. X Kranggan District, Temanggung Regency - Kariyanti, Maidira; Budiono, Irwan; Maharani, Chatila (Public Health Perspective Journal, 2024)
Exclusive breastfeeding is the best nutrition for babies, but its coverage in Indonesia remains low, including in Temanggung Regency. Working mothers, especially in large industries like PT. X, often face challenges due to facility constraints, company policies, and other factors. This study aims to identify factors related to exclusive breastfeeding among working mothers at PT. X, Kranggan District, Temanggung Regency. It is an observational quantitative study with a crosssectional design conducted via direct interviews with 56 plywood worker respondents at PT. X using a validated questionnaire. The results showed a significant relationship between exclusive breastfeeding and educational attainment (p=0.028), parity (p=0.042), duration of work (p=0.024) and family support (p=0.004). However, no significant relationship was found with knowledge (p= 0.080), maternal attitudes towards exclusive breastfeeding (p=0.086), maternal age (p=0.367), availability of breastfeeding facilities (p=0.091), distance traveled from home to work (p=0.104), travel time from home to workplace (p=0.280), husband support (p=0.086), co-worker support (p=0.080) and health worker support at work (p=0.101). The multivariate model revealed that education level (p=0.019), length of work (p=0.035), and occupational health workforce support (p=0.050) were the most influential factors. This study concludes that education, length of employment, and support of health workers in the workplace have a significant effect on exclusive breastfeeding at PT. X, Kranggan District, Temanggung Regency.